Relationship between p53-associated proteins and estrogen receptor status in ovarian serous neoplasms. Issue 3 (1st April 2006) - Cho, E. Y.; Choi, Y. L.; Chae, S. W.; Sohn, J. H.; Ahn, G. H.
Abstract : We studied the immunoexpression of p14ARF, MDM2, and p53, in addition to relationships between those protein expressions and estrogen receptor (ER)α in ovarian serous tumors including benign ( n = 23), borderline ( n = 41), and malignant ( n = 94). The aberrant expressions of p14ARF, MDM2, and p53 were observed in 19.6% (31/158), 47.5% (75/158), and 39.9% (63/158) of cases, respectively. The expression of MDM2 was significantly higher in borderline tumors compared to benign ( P = 0.04) and malignant ( P < 0.01) tumors. p53 expression in borderline tumors was uncommon, and p14ARF expression loss was mainly observed in carcinomas. Altered expression of p14ARF, MDM2, and p53 shows significant relationship with stage. Overexpression of MDM2 ( P = 0.01) and loss of p14ARF expression ( P = 0.04) were significantly associated with ER expression. Our results suggest that alteration of p14ARF–MDM2–p53 pathway proteins may contribute significantly to the tumorigenesis of ovarian serous neoplasms, and ER is involved in cellular regulation of p14ARF–MDM2–p53 pathway in ovarian serous neoplasms.